2018
DOI: 10.1242/dev.158519
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule organization in presynaptic boutons relies on the formin DAAM

Abstract: Regulation of the cytoskeleton is fundamental to the development and function of synaptic terminals, such as neuromuscular junctions. Despite the identification of numerous proteins that regulate synaptic actin and microtubule dynamics, the mechanisms of cytoskeletal control during terminal arbor formation have remained largely elusive. Here, we show that DAAM, a member of the formin family of cytoskeleton organizing factors, is an important presynaptic regulator of neuromuscular junction development in Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…For proteomic analysis, the gel was stained with Coomassie Brilliant Blue then destained with the mix of 40% ethanol and 10% acetic acid. The 50-65 kDa region of the soluble and insoluble sample were subjected to in-gel digestion as described in Migh et al [48]. Briefly, protein disulfide bridges were reduced with dithiothreitol (30 min, 56°C) then the resulting sulfhydryl groups were capped using iodoacetamide (30 min, RT, in the dark) following digestion with sequencing grade side chain protected trypsin (4h, 37°C).…”
Section: Methodsmentioning
confidence: 99%
“…For proteomic analysis, the gel was stained with Coomassie Brilliant Blue then destained with the mix of 40% ethanol and 10% acetic acid. The 50-65 kDa region of the soluble and insoluble sample were subjected to in-gel digestion as described in Migh et al [48]. Briefly, protein disulfide bridges were reduced with dithiothreitol (30 min, 56°C) then the resulting sulfhydryl groups were capped using iodoacetamide (30 min, RT, in the dark) following digestion with sequencing grade side chain protected trypsin (4h, 37°C).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest a model where increased stabilization of MTs is associated with increased NMJ expansion. Additional factors that are associated with MT stability, such as the formins Diaphanous (Pawson, Eaton, & Davis, ) and DAAM (Bartolini & Gundersen, ; Migh et al, ), have also been found to promote NMJ expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies, however, have explored these possibilities using modern imaging approaches. Presynaptic MAP-associated stable MT loops, EB1-labeled dynamic pioneer MTs, and DAAM-dependent stable MT regulation of SV release and AZ morphology have been described at the Drosophila neuromuscular junction (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%